Prinsip Kehati-Hatian Bank dalam Penyaluran Kredit Untuk Mencegah Tindak Pidana Korupsi - Prasanti Ratnaningrum; Dudik Djaja S (Wajah Hukum, 2023)
Even though banking itself has the principle of prudence in every activity, this will not close the gap for corruption. The purpose of this study is to analyze the principles of bank prudence in lending to prevent criminal acts of corruption and analyze the prosecution and consideration of judges' sanctions in giving decisions on corruption in lending. In this study, there are three research approaches used, namely the statutory approach, the conceptual approach, and the case approach. Data is analyzed by identifying legal facts and eliminating irrelevant matters, collecting legal materials and non-legal materials, conducting a review of the proposed legal issues, accepting conclusions, and providing prescriptions. The results of this study indicate that the precautionary principles of banks in extending credit to prevent corruption are regulated in Article 8 of the Banking Law as amended by Law Number 10 of 1998, specifically regarding the explanation of Article 8 paragraph (1) . In terms of enforcement and considering the judge's sanctions in giving a decision on corruption in the distribution of credit, the judge at least looks at two things, namely if the defendant violates the principle of prudence and there is clear evidence that the defendant took advantage of his actions, then the defendant will be charged with an article on corruption. If the defendant violates the precautionary principle but is not proven to have actually taken personal advantage from his actions, the judge decides that the defendant has violated the Banking Law and not a criminal act of corruption.